2019
DOI: 10.3390/life9020043
|View full text |Cite
|
Sign up to set email alerts
|

Phosphates as Energy Sources to Expand Metabolic Networks

Abstract: Phosphates are essential for modern metabolisms. A recent study reported a phosphate-free metabolic network and suggested that thioesters, rather than phosphates, could alleviate thermodynamic bottlenecks of network expansion. As a result, it was considered that a phosphorus-independent metabolism could exist before the phosphate-based genetic coding system. To explore the origin of phosphorus-dependent metabolism, the present study constructs a protometabolic network that contains phosphates prebiotically ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…These functions are also not greatly influenced by the change in temperature (Figure 2B and Figure S1B, and Table S3). When including the reactions without accurate free energy estimation, the scale of the phosphate-dependent network obtained at −25 °C is close to the thermodynamically constrained network constructed in our previous study (360 vs. 338 metabolites) [15]. At this temperature, this network is mainly composed of reactions that participate in glycolysis, the tricarboxylic acid (TCA) cycle, and carbon fixation, which supply the basic carbohydrates and energy to living systems.…”
Section: Resultssupporting
confidence: 77%
“…These functions are also not greatly influenced by the change in temperature (Figure 2B and Figure S1B, and Table S3). When including the reactions without accurate free energy estimation, the scale of the phosphate-dependent network obtained at −25 °C is close to the thermodynamically constrained network constructed in our previous study (360 vs. 338 metabolites) [15]. At this temperature, this network is mainly composed of reactions that participate in glycolysis, the tricarboxylic acid (TCA) cycle, and carbon fixation, which supply the basic carbohydrates and energy to living systems.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, LCO NPs have been shown previously to adsorb phosphate in solution. 35,36 As phosphates are a crucial component in metabolism, 53 among many other cellular functions, a depletion of phosphate due to sorption onto the NPs might disrupt metabolic balance and explain the upregulation of metabolic pathways observed here. Additionally, nanomaterials such as gold, 54 platinum, 55 and titanium dioxide 56 have been shown previously to catalyze the oxidation of NADH to NAD + .…”
Section: Subtoxic and Toxic Np Doses Upregulate Pathways That Fall Inmentioning
confidence: 87%
“…It is possible that thioester and polyphosphate-driven chemistries were both required from the outset in order to circumvent thermodynamic bottlenecks. 181 Prebiotic sources of phosphate and prebiotic means of phosphorylation have been the subject of investigation for a long time and have recently been reviewed. [182][183][184] However, studies on non-enzymatic versions of the phosphorylation reactions found in core metabolic pathways remains rare, with a notable exception being the phosphorylation of adenosine, AMP or ADP to ATP.…”
Section: Summary and Future Directionsmentioning
confidence: 99%